The Logic Of Phallus And Object Of Desire: Rethinking ‘Masculinities’ in Literary Works of Contemporary Indonesian Woman Writers - Achmad Fawaid (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2021)
The recent studies commonly pointed out that literary works of contemporary Indonesian women writers have coined feminist ideology. However, the study on reading these writers in ‘masculine’ perspective is rarely given. This study amins to analyze the works of two important Indonesian women writers, Ayu Utami and Djenar Maesa Ayu to demonstrate the inadequate definition of labels 'masculine' and 'feminine’ as binary opposition between male and female for explaining a much more fundamental problem: desire. This study concluded that first, the short stories of Ayu Utami and Djenar Maesa Utami demonstrate—in Connell's terminology—the master signifier or—in Lacan's terminology—phallic desire towards male, meaning that, instead of being regarded as